2005
DOI: 10.1063/1.1840094
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar space-charge limited current through layers with a disparate concentration of shallow traps: Experiment and model

Abstract: Interpretation of trap-limited mobility in space-charge limited current in organic layers with exponential density of traps J. Appl. Phys. 110, 043705 (2011); 10.1063/1.3622615 Space-charge limited conduction in doped polypyrrole devices J. Appl. Phys. 107, 093716 (2010); 10.1063/1.3373393Field-dependent mobility from space-charge-limited current-voltage curvesThe influence of the spatial distribution of trap states on unipolar space-charge limited current ͑SCLC͒ is investigated experimentally and theoreticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As can be seen, it includes three distinct regimes: (1) Ohmic, (2) trap-filled space charge limited current (TF-SCLC), and (3) trap-filled limit current (TFL-SCLC) regimes. 31,32 This indicated that traps which inevitably formed during device fabrication process existed at low injection current but some new traps were formed at higher injection currents. According to the reports in the literatures, the amounts of traps can increase with decreasing temperature, 29 and physical defects of the devices reduce the free triplet lifetime and can also reduce the intensity of delayed fluorescence by immobilizing the triplet excitons.…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen, it includes three distinct regimes: (1) Ohmic, (2) trap-filled space charge limited current (TF-SCLC), and (3) trap-filled limit current (TFL-SCLC) regimes. 31,32 This indicated that traps which inevitably formed during device fabrication process existed at low injection current but some new traps were formed at higher injection currents. According to the reports in the literatures, the amounts of traps can increase with decreasing temperature, 29 and physical defects of the devices reduce the free triplet lifetime and can also reduce the intensity of delayed fluorescence by immobilizing the triplet excitons.…”
Section: Methodsmentioning
confidence: 99%
“…7 This renders ␣-NPD doped with 1-NaphDATA a good model system for investigating the effect of hole traps on hole charge transport. 8 Few microns of the organic semiconductors are deposited by thermal coevaporation at a base pressure of 10 −6 mbar onto a 10-nm-thick semitransparent Al electrode on a glass substrate and are topped with a thick Al counter electrode. The time-of-flight measurements 9 are carried out utilizing a frequency-tripled Nd:YAG ͑yttrium aluminum garnet͒ laser ͑Solar Systems LQ129/LQ103͒ at a wavelength of 355 nm and a pulse length of 10 ns, which is used to excite an electrode-near regime of the organic layer through the semitransparent Al electrode.…”
mentioning
confidence: 99%
“…With increasing the positive applied voltage, electrons are injected into SiO x from the surface inversion layer of p-Si substrate, which will fill the discrete energy levels in band gap of SiO x to form a certain space charge distribution, which will be responsible for the trap-filled-limited SCLC (TFL-SCLC) [29,30]. Based on the Poisson's equation and current continuity equation, for single trap level, the TFL-SCLC is proportional to the square of voltage, i.e.…”
Section: I-v Curve Fitting and Carrier Transport Mechanism For Device...mentioning
confidence: 99%